P-D10 Differential induction of anti-V3 crown antibodies with cradle and ladle-binding modes in response to HIV-1 envelope vaccination. (January 2016) - Balasubramanian, Preetha; Kumar, Rajnish; Williams, Constance; Itri, Vincenza; Wnag, Shixia; Lu, Shan; Hesell, Ann; Sinangil, Faruk; Higgins, Keith; Liu, Lily; Haigwood, Nancy; Gorny, Miroslaw; et al.
Abstract : The V3 loop in the HIV-1 envelope glycoprotein gp120 is one of the key targets for neutralizing antibodies (Abs). The V3 crown in particular has conserved structural elements that are targeted by neutralizing Abs. Two Ab-V3 binding modes, designated cradle and ladle, have been identified based on many X-ray crystal structures of human anti-V3 mAbs from HIV- infected patients. Anti-V3 Abs with the cradle-binding mode use mainly the VH5-51 genes, while those with the ladle-binding mode use various VH1-VH4 family genes. However, very little is known about the types of anti-V3 Abs induced by vaccination. In this study, first we examined the V3 Abs induced in human vaccinees in the VAX003 (B/E) and VAX004 (B/B) trials who received bivalent recombinant gp120 protein vaccines. Our data show that the titers of anti-V3 Abs with either cradle or ladle binding modes were relatively low in the sera of these vaccinees, but a higher percentage of responders were observed in VAX004 than VAX003. In both trials, a higher percentage of responders generated Abs using the cradle-binding mode than Abs with the ladle-binding mode. When we compared with other species, like macaques and rabbits, the percentage of animals that produced Abs with the V3 cradle mode were again higher compared to those producing the V3 ladle-mode Abs, regardless of the envelope subtypes used in vaccine. In contrast, BALB/c mice immunized with HIV envelope proteins generated V3 Abs of only the ladle-binding mode and not of cradle binding mode. We further showed that most, but not all, V3 Abs of cradle-binding mode produced in humans, macaques and rabbits mediated virus neutralization. V3 ladle-binding Abs from mice also mediated virus neutralization. Hence, both V3 cradle-binding and ladle-binding Abs can mediate virus neutralization. Altogether, our data demonstrate differences in the fine specificity of V3 Abs generated in humans and animal models upon immunization of HIV envelope.